2014
DOI: 10.1097/qai.0000000000000171
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Returning to HIV Care After a Gap in Care in New York State

Abstract: Background Retention in HIV care has important implications. Few studies examining retention include comprehensive and heterogeneous populations, and few examine factors associated with returning to care after gaps in care. We identified reasons for gaps in care and factors associated with returning to care. Methods We extracted medical record and state-wide reporting data from 1865 patients with one HIV visit to a New York facility in 2008 and subsequent 6-month gap in care. Using mixed effect logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
(39 reference statements)
3
19
2
1
Order By: Relevance
“…14,[16][17][18][19] However, despite this finding, we found that, compared with women in care, both seekers and nonseekers were no more likely to perceive lack of health insurance as a barrier to care. Although prior studies have found drug use to be associated with poor engagement in care, 14,16,19,[21][22][23][24][25] we found that, compared with women in care, only non-seekers were more likely to report high-risk drug use and sexual behaviors. As this subgroup was less likely to report transportation as a barrier to care and was no more likely to report other structural barriers to care as women in care, our findings suggest that this subgroup of women may not report barriers because they are not actively seeking HIV medical care.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…14,[16][17][18][19] However, despite this finding, we found that, compared with women in care, both seekers and nonseekers were no more likely to perceive lack of health insurance as a barrier to care. Although prior studies have found drug use to be associated with poor engagement in care, 14,16,19,[21][22][23][24][25] we found that, compared with women in care, only non-seekers were more likely to report high-risk drug use and sexual behaviors. As this subgroup was less likely to report transportation as a barrier to care and was no more likely to report other structural barriers to care as women in care, our findings suggest that this subgroup of women may not report barriers because they are not actively seeking HIV medical care.…”
Section: Discussioncontrasting
confidence: 76%
“…Consequently, they are at high risk for poor health outcomes and for transmitting HIV to others. [4][5][6][7][8][9][10] Although prior studies have identified numerous factors associated with poor engagement in care (e.g., lack of transportation [11][12][13] and health insurance, [14][15][16][17][18][19] caregiving responsibilities, 13,20 depression, 13,16,21 and substance use 14,16,19,[21][22][23][24][25], these studies have been limited in two important respects. First, many have viewed those who are not engaged in care as a single, homogenous group, failing to recognize potentially nuanced differences among women that may help to inform the development of targeted interventions.…”
Section: Introductionmentioning
confidence: 99%
“…First, we did not have data on income, education, employment, insurance coverage, or other contextual and social factors that have been associated with both retention and HIV disease outcomes in other studies and that may differ by demographic factors or HIV transmission risk group. 39,40 Some studies with single-sex populations have noted that poverty and housing instability reduce retention and ART adherence. 41,42 We maintain that the absence of these data has been mitigated by the fact that all patients under study were successfully engaged in care (a prerequisite for the NA-ACCORD) and had access to ART.…”
Section: Discussionmentioning
confidence: 99%
“…Others are individual-level characteristics including substance abuse (15,19,21,22); younger age (2224); depression and mental distress (14,17,19); having less advanced HIV disease (22,25); and misconceptions about HIV treatment (26). By contrast, factors found to facilitate HIV care linkage, engagement, and retention include integrated social and health care services and perceived support from providers (15,19,27–29); case management and care navigation (19,28,30); housing assistance (31,32); social support (19,33); and perceiving a responsibility to take care of one’s family (18). …”
Section: Introductionmentioning
confidence: 99%